Some Charged Fluid Spheres in General Relativity: Solutions and Conditions for Charged Fluid Spheres in General Relativity (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The present paper provides some solutions of Einstein Maxwell field equations for SomeCharged Fluid Spheres by using a judicious choice of metric potential g11 and g44. The central andboundary conditions have been also discussed